TOURISM ADVERTISEMENT SEMIOTIC OF HUNI RAYA GROUP INSTAGRAM POST - M. Nashoihul Ibad (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2021)
Abstract This article explores the semiotics of CV's Instagram content. Huni Raya is a medium of advertising travel services that it offers to internet users / to obtain consumers. This research aims to uncover the persuasive meaning of CV Instagram posts. Huni Raya to attract tourist consumers to Bromo. This research included qualitative research using John Fiske's semiotics theory. The analysis unit studied is a persuasive message in a CV Instagram post. Huni Raya, Representative from the point of view of photography results and the meaning that Bromo Tourism is beautiful and beautiful so it is very good for tourists to visit. Data was obtained using observation, interviews, and studies of relevant literature by the formulation of the problem. Based on the data obtained, the results of this study explain the meaning of persuasive messages in CV post ads. Huni Raya shows the beauty and beauty of Bromo is very worthy to be used as a tourist spot. Tourism in Bromo some values make tourists can feel the natural nuances, the beauty of sunrise, tranquility, refreshing the brain. The results of advertising photography on Instagram CV. Huni Raya is good enough and satisfying to attract consumers to Bromo.